The Audio-Tape Recording of Counselling Sessions - Andrews, W. Robin; Johnston, C. Fred (Canadian Journal of Counselling and Psychotherapy, 1980)
Practical suggestions are offered with the objectives of helping counsellors to produce satisfactory audio-tape recordings of individual and group counselling sessions, to derive maximum benefit from the recording of counselling interviews, and to tape record in an ethical manner and without undue stress.